2002
DOI: 10.1002/0471142913.fag0107s06
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Mouth Conditions for Flavor Analysis

Abstract: This unit discusses the use and design of the two mouth simulators, the retronasal aroma simulator (RAS) and the model mouth, that have successfully been verified to produce an effluent with volatile ratios similar to that found in human exhaled breath during eating. Though at a glance the apparatuses seem very different, they produce relatively similar effluents. Of obvious notability is the difference in the size of the reservoir; the RAS reservoir is 1 liter and the model mouth reservoir is 70 ml. When dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Saliva influences the volatility of some compounds when a food is chewed, because it dilutes the sample (food), affects the pH and may affect the binding aroma compounds through the action of the enzymes present [9]. In the present study, it was observed that the composition of the HS with the sausage alone (orthonasal aroma) differed when artificial saliva was added (simulation of retronasal aroma).…”
Section: Comparison Of Sift-ms and Spme-gc-ms Applied To Fermented Samentioning
confidence: 60%
See 4 more Smart Citations
“…Saliva influences the volatility of some compounds when a food is chewed, because it dilutes the sample (food), affects the pH and may affect the binding aroma compounds through the action of the enzymes present [9]. In the present study, it was observed that the composition of the HS with the sausage alone (orthonasal aroma) differed when artificial saliva was added (simulation of retronasal aroma).…”
Section: Comparison Of Sift-ms and Spme-gc-ms Applied To Fermented Samentioning
confidence: 60%
“…However, saliva is only one of the factors that affect the release of volatile compounds when eating food. Also involved are mouth temperature, mastication rate and breath flow [9]. The present experiments are a preliminary study of aroma perception during eating and further research by exploiting SIFT-MS for real-time studies of flavour release (direct nosespace analysis) would surely be very productive.…”
Section: Comparison Of Sift-ms and Spme-gc-ms Applied To Fermented Samentioning
confidence: 98%
See 3 more Smart Citations